Construction pollution in Brunei. (October 2019) - Rahman, M M; Yusof, I B H M; Asli, R A
Abstract: Despite its considerable contribution to the economy of a country, construction industry is held responsible for degrading sustainability in general, and environment in particular, in many ways. For example, it consumes about 40% of global resources and, generates almost half of all the pollution. However, their nature and degree may vary according to the type and scale of the projects, and often can be area or country specific. Especially, no research seems to have been conducted previously in Brunei Darussalam for identifying pollution from construction. Therefore, this study was undertaken to identify sources of construction related pollution and their mitigating strategies. However, this paper focuses only on sources of pollution and summarizes the outcomes from a questionnaire survey of 107 responses, comprising clients, contractors and consultants. Five groups of pollution were identified, with various sources within each group: air pollution that includes dust and GHG (greenhouse gas), water pollution, noise pollution, and solid waste. All the sources were observed to have different degrees of criticality, i.e. either critical or more critical, implying a general critically of the identified sources of pollution. However, the focus seems to be on developing an industry wide awareness towards pollution, with contractors to play key role to pollution and relevant activities, probably due to their engagement in executing construction at sites. The next step of the study is to further investigate for a holistic solution, while the outcomes are expected to help policymakers to develop and/or take appropriate measures to control pollution.